Tecnologia dell'architettura: creatività e innovazione nella ricerca Materiali del I Seminario OSDOTTA (Viareggio, 14-16 settembre 2005) - Maria Antonietta Esposito (Scuole di dottorato, 2006)
This book is the first in a series conceived to valorise the activity carried out within the Research and Technology of Architecture Doctorates, through the presentation of the results of the first seminar of the Italian doctorates. The educational and scientific significance of this innovative experience is witnessed by the contributions and the issues tackled, which map out the scenario of the research and the proposals for the future. For this reason the book - and the entire series - are also proposed with a multi-level educational function (orienting those approaching the subject in terms of the contents tackled by the sector in Italy) and as a tool for professional updating directed at the achievement of the most elevated quality levels.